Effective tax rates, endogenous mark-ups and heterogeneous firms - Michael Irlacher; Florian Unger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2018)
We provide a new explanation why effective tax rates are smaller for larger firms even in the absence of common channels like profit shifting and lobbying. This result emerges in a heterogeneous firms model with endogenous mark-ups. Our framework features imperfect tax pass-through into prices and partial deductibility of production costs. Corporate taxes reduce mark-ups and hence pre-tax profits, especially for high cost firms. As production costs are only partially deductible, high cost producers are affected most by taxes. We further show that shocks which affect mark-ups through competition, like globalization, reinforce the heterogeneity in effective tax rates across firms.
urn:nbn:de:bvb:19-epub-49717-5
Keywords: H25; F12; L11; 330; Heterogeneous firms; Corporate taxation; Effective tax rate; Linear demand; Endogenous mark-ups